Prevention of Fraud with the Values of Suport Approach - Yanuar, Fuad; Yuri, Jennifer; Chew, Maykoski; Torsten, Pafgett (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
The Sufism value approach emphasizes the importance of honesty, integrity, responsibility and cooperation in business. These values ??teach that everyone is responsible for their actions and respects the interests of others. In this case, Sufism values ??can help prevent fraud by encouraging people to behave honestly and responsibly in all situations. In fraud prevention, Sufism values ??can be implemented in various ways. For example, a company can develop a code of ethics based on Islamic moral principles and teach it to its employees. Companies can also implement training programs emphasizing honesty, integrity and responsibility in business. In addition, the value approach of Sufism can help build better relationships between companies and clients because these values ??encourage companies to act fairly and responsibly towards the interests of their clients. This can help prevent fraud committed by parties in a business relationship. In conclusion, the tasawuf value approach can effectively prevent fraud in the business and financial world. By implementing Islamic moral and ethical values, companies can build a work culture of integrity, honesty and responsibility and improve client relationships.